A Delphi Study of Socio-Cognitive Predictors of Career Choice Behavior in the Construction Industry in South Africa - Mariam Akinlolu; Theo C. Haupt (Journal of Construction Project Management and Innovation)
This paper presents findings of a Delphi study which sought to identify the key factors that influence and determine the career choices of women in the construction industry in the South African context. Adopting the Socio-Cognitive Career Theory (SCCT) as the study’s conceptual framework, a two-round iteration was performed to obtain the opinion of 14 experts actively involved in the South African construction industry. Consensus was achieved on ten predictors and 53 elements that influenced women’s decisions to undertake a career in the construction profession. Findings from the study revealed women’s career choices were influenced by gender, self-efficacy, socio-economic status, outcome expectations, goal representations, learning experiences, interests, social supports, perceived barriers and access to opportunity structures. Ethnicity was found to have insignificant importance and impact on their career choices. The implication of the research is that results from the study provides insight into the factors that could conceivably increase the participation of women who want to enter and remain in the construction work.